The ethics of climate‐induced community displacement and resettlement. (16th April 2018) - Draper, Jamie; McKinnon, Catriona
Abstract : Climate‐induced resettlement programs are happening right now in places around the world where populations face high risks from climatic impacts. Burgeoning literatures are considering the ethical implications of climate change more broadly, and the ethics of migration, but the nexus between the two issues has not been given enough attention by moral and political theorists, especially with respect to climate‐induced community resettlement. Here, we sketch the key nodes in a debate we think should take place, which will be made even more urgent in the coming decades as climate change impacts on communities least resilient to it. This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice